2012
DOI: 10.1017/s0144686x11001152
|View full text |Cite
|
Sign up to set email alerts
|

On the track of evaluated programmes targeting the social participation of seniors: a typology proposal

Abstract: Nowadays, the social participation of seniors represents a central challenge for both individuals and collectivities. The participative perspective is indeed present in most of the contemporary discourses on ageing, and is viewed both as a way to manage the current demographic juncture and as a promising direction for enhancing seniors’ wellbeing and achievements. This article examines 32 programmes aimed at fostering the social participation of seniors that were both implemented and evaluated, and whose resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 54 publications
4
34
0
6
Order By: Relevance
“…Poscia, et al [34] and Cattan, et al [10]. The remaining five reviews focused on loneliness and other outcomes of interests such as anxiety and depression (n = 3); or other related concepts such as social participation [56], and social connectedness [35]. While there is a distinction between loneliness and social isolation, there was not any obvious differences in reviews that focused on loneliness or social isolation in terms of the review type, where the research was conducted, and how the findings were reported.…”
Section: Concept Of Loneliness and Social Isolationmentioning
confidence: 99%
“…Poscia, et al [34] and Cattan, et al [10]. The remaining five reviews focused on loneliness and other outcomes of interests such as anxiety and depression (n = 3); or other related concepts such as social participation [56], and social connectedness [35]. While there is a distinction between loneliness and social isolation, there was not any obvious differences in reviews that focused on loneliness or social isolation in terms of the review type, where the research was conducted, and how the findings were reported.…”
Section: Concept Of Loneliness and Social Isolationmentioning
confidence: 99%
“…To our knowledge, this action research is the rst to identify and prioritize the social participation needs of older adults living in a rural RCM using a process in which stakeholders played a signi cant role. In accordance with the guidelines of Raymond and colleagues [9], this action research directly involved older adults, caregivers and community members from many different backgrounds, and therefore provides an inclusive understanding of the needs of older adults in a rural RCM. The study was based on a strong partnership with the community and involved a personalized approach to the experiences and cultures of older adults in the RCM.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Some trials achieved significant effects on several health outcomes while others have not,17–20 and an overview of trials that promote social capital is lacking. Previous systematic reviews have generally included non-randomised designs21–24 and focused interventions on specific social capital components25 26 or psychosocial interventions 24 27. Moreover, they have assessed psychosocial effects and seldom considered health outcomes 22…”
Section: Introductionmentioning
confidence: 99%